Understanding of the life experience of homeless women - Priscilla Ribeiro Biscotto; Maria Cristina Pinto de Jesus; Marcelo Henrique da Silva; Deíse Moura de Oliveira; Miriam Aparecida Barbosa Merighi
Abstract OBJECTIVE To understand the life experience of homeless women. METHOD A social phenomenological study was conducted with 10 women assisted by a shelter. The analysis of the interviews was based on the theoretical framework of social phenomenology of Alfred Schütz and thematic literature. RESULTS The participants face adversities in the street context, with emphasis on the risk of physical and sexual abuse, and seek shelters as a possibility for minimizing difficulties experienced. They hope to leave the streets; however, they see themselves trapped in this social reality, due to the addiction to alcohol and other drugs. CONCLUSION The understanding of the life experience of homeless women shows daily confrontations and reveals the conflict between the desire for leaving and remaining on the streets, given the complexity of the reality that keeps them in this condition.